KEPERIBADIAN DAN KARAKTER GURU PENDIDIKAN AGAMA ISLAM - Iroh Suhiroh; Naf’an Tarihoran (Journal of Innovation Research and Knowledge, 2022)
Based on Law no. 20 of 2003 concerning the National Education System (SISDIKNAS) The purpose of National Education is to develop the potential of students to become human beings who believe and fear God Almighty, have noble character, are healthy, knowledgeable, capable, creative, independent and become democratic and responsible citizens. . However, nowadays, there is a tendency for most teachers to only think that their main task is only to transfer knowledge cognitively, lacking in embedding the values ​​contained in the scientific material they convey. This is coupled with the teaching conditions oriented to the numbers as a standardization of the success of the education process. In fact, the ideal is that a teacher with good character and noble character will give birth to students with noble personality and noble character. For this reason, this paper will briefly discuss the Personality and Character of Islamic Religious Education Teachers. As well as how a teacher's efforts to build student character and the factors that influence the personality and character of the teacher.